The Relationship Between Islam and Local Traditions at Pondok Buntet Pesantren, Cirebon, West Java - Naila Farah; Ahmad Rifki; Dewi Safitri (Journal of Religion and Social Transformation, 2026)
This article examines the relationship between Islamic teachings and local traditions as practiced at Pondok Buntet Pesantren, one of the oldest Islamic educational institutions in Cirebon, West Java. The study aims to explore how this pesantren integrates Islamic values with local wisdom that has long been embedded in the cultural life of the Cirebonese community. A qualitative approach is employed, utilizing observation, in-depth interviews, and document analysis as the primary methods of data collection. The findings indicate that Pondok Buntet Pesantren implements a strategy of cultural acculturation by accommodating local traditions such as customary rituals and traditional arts within Islamic teachings without compromising the fundamental principles of Islamic law. This approach not only strengthens the Islamic identity of the community but also preserves local traditions as an integral part of the nation’s cultural heritage. The article underscores the importance of an inclusive approach to Islamic da‘wah in fostering harmony between religion and local culture, particularly in regions with a long history of cultural pluralism such as Cirebon.